Kate Beswick - unknown:::Creator::::::::::::
Katherine Beswick, a fellow Stanford student with whom Steinbeck corresponded extensively in the late 1920s. Beswick critiqued his work and offered to support Steinbeck until he could get on his feet. This photo is from the Stanford Quad yearbook.